2018
DOI: 10.1080/08985626.2018.1537147
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive technology adoption, particularities of clustered firms

Abstract: This paper explores to what extent the internal attributes of a clustered firm influence its capacity to adopt a disruptive innovation. A multidimensional approach to the absorptive capacity (ACAP) model is used to distinguish between potential (acquisition and assimilation domains) and realized (transformation and exploitation domains) internal firm capabilities. Our evidence come from an empirical analysis of the firm population belonging to the Spanish ceramic tile cluster who have massively adopted a disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Extant studies have shown that it is possible to enhance firms' operational efficiency via technological intervention [Ahuja et al, 2020;Ain et al, 2019;Nam et al, 2019]. Since a potentially disruptive technology is capable of overcoming supply chain barriers, it can boost a firm's performance and efficiency in carrying out various functions [Saberi et al, 2019;Molina-Morales et al, 2019]. Similarly, studies have shown that due to the ripple effects, using outdated and inefficient technology can hamper business efficiency, effectiveness, and performance [Yeniyurt et al, 2019;Dowlatshahi, Cao, 2006].…”
Section: Technology Adoption and Operational Efficiencymentioning
confidence: 99%
“…Extant studies have shown that it is possible to enhance firms' operational efficiency via technological intervention [Ahuja et al, 2020;Ain et al, 2019;Nam et al, 2019]. Since a potentially disruptive technology is capable of overcoming supply chain barriers, it can boost a firm's performance and efficiency in carrying out various functions [Saberi et al, 2019;Molina-Morales et al, 2019]. Similarly, studies have shown that due to the ripple effects, using outdated and inefficient technology can hamper business efficiency, effectiveness, and performance [Yeniyurt et al, 2019;Dowlatshahi, Cao, 2006].…”
Section: Technology Adoption and Operational Efficiencymentioning
confidence: 99%
“…Early adopters of I4.0 technologies, who are highly oriented toward implementing early-stage technologies, that work in clusters, can also multiply the likelihood of adoption by 473.7 per cent. The grouping process in clusters generates tacit knowledge and exchange of high-quality information, hence promoting innovation [23].…”
Section: Innovation and Digital Culturementioning
confidence: 99%
“…"Absorptive Capacity" moderates the relationship between social capital and the adoption process [1]. When the absorptive capacity" is high in organizations, it directly affects the adoption of I4.0 technologies [23]. Moreover, the "Exploratory Absorptive Capacity", i.e.…”
Section: Absorptive Capacitymentioning
confidence: 99%
See 2 more Smart Citations